Circularly polarized luminescent material based on rare earth upconversion nanocrystals and preparation method thereof

CN118496858BActive Publication Date: 2026-10-16FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310112710.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-14
Publication Date
2026-10-16
Estimated Expiration
2043-02-14

AI Technical Summary

Technical Problem

然而,目前基于稀土上转换纳米晶的圆偏振发光材料仍鲜有报道,建立一种普适性的合成制备策略并实现非手性稀土上转换纳米晶的圆偏振发光,对于拓展稀土无机纳米材料在3D显示、手性识别、生物医学等领域的相关研究,具有较好的参考意义与应用价值

Benefits of technology

[0059] (1) The present invention provides a method for preparing a circularly polarized luminescent material, wherein the method can achieve upconversion circularly polarized luminescence of non-chiral upconversion nanocrystals through molecular self-assembly in rare earth upconversion nanocrystals and chiral template hydrogels;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118496858B_ABST
    Figure CN118496858B_ABST
Patent Text Reader

Abstract

The application discloses a circularly polarized luminescent material based on a rare earth upconversion nanocrystal and a preparation method thereof. The luminescent material is obtained by co-assembly of a chiral template and an upconversion nanocrystal, so that the upconversion nanocrystal obtains chirality. The application further provides a preparation method of the luminescent material, which can realize emission of upconversion circularly polarized light of multiple wave bands and CPL luminescence of non-chiral upconversion nanoparticles in multiple wave bands in a visible light region.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of luminescent materials technology, specifically relating to a circularly polarized luminescent material based on rare-earth upconversion nanocrystals and its preparation method. Background Technology

[0002] Rare-earth-doped upconversion luminescent materials (UCNPs) are a class of inorganic nanomaterials doped with rare-earth elements. Upconversion luminescence is a nonlinear optical process that converts two or more low-energy photons into one high-energy photon. Due to the abundant electronic energy level structure of rare-earth ions and the numerous transitions between energy levels, upconversion luminescence can be achieved across a wide wavelength range from ultraviolet to infrared. Upconversion luminescence is generally excited by near-infrared lasers, thus possessing advantages such as high light penetration depth, high spatial resolution, absence of biological background fluorescence interference, and minimal sample damage. Therefore, it has broad application prospects in fields such as biosensing, lasers, and 3D displays. Circularly polarized luminescence has enormous potential applications in optical information processing, display, storage, and biochemistry. However, there are currently few reports on circularly polarized luminescent materials based on rare-earth upconversion nanocrystals. Establishing a universal synthesis strategy and realizing circularly polarized luminescence of non-chiral rare-earth upconversion nanocrystals would have significant reference and application value for expanding the research on rare-earth inorganic nanomaterials in fields such as 3D displays, chiral recognition, and biomedicine. Summary of the Invention

[0003] To address the aforementioned technical problems, the present invention provides the following technical solution:

[0004] A luminescent material is obtained by co-assembling a chiral template and upconversion nanocrystals, thereby giving the upconversion nanocrystals chirality.

[0005] According to an embodiment of the present invention, the upconversion nanocrystals are uniform in size, and their particle size is selected from 1-100 nm, for example 10-20 nm, 30 nm, or 50 nm.

[0006] According to an embodiment of the present invention, the upconversion nanocrystals include a matrix material, activating ions, and sensitizing ions.

[0007] According to an embodiment of the present invention, the matrix material is selected from rare earth fluorides and / or oxides, such as at least one of NaYF4, NaGdF4, NaLuF4, LiYF4, LiYbF4, Y2O3, Lu2O3, etc.

[0008] According to an embodiment of the present invention, the sensitizing ion is selected from Yb. 3+ Ce 3+ 、Nd 3+ Gd 3+ Y 3+At least one of the following.

[0009] According to an embodiment of the present invention, the activating ion is selected from Tm 3+ Er 3+ Ho 3+ 、Sm 3+ Eu 3+ 、Tb 3+ Dy 3+ At least one of the following.

[0010] According to an embodiment of the present invention, the molecular formula of the upconversion nanocrystals is ABF4:(M,N), wherein,

[0011] A is selected from at least one of Na, Li, K, etc.;

[0012] B is selected from at least one or more of the following: lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, yttrium, and scandium.

[0013] M is the activating ion, selected from Tm. 3+ Er 3+ Ho 3+ 、Sm 3+ Eu 3+ 、Tb 3+ Dy 3+ At least one of the following.

[0014] N is the sensitizing ion, selected from Yb. 3+ Ce 3+ 、Nd 3+ Gd 3+ Y 3+ At least one of the following.

[0015] According to an embodiment of the present invention, the activating ions are provided by an activation ion source, such as Tm. 3+ Er 3+ Ho 3+ 、Sm 3+ Eu 3+ 、Tb 3+ Dy 3+ At least one of the acetates.

[0016] According to an embodiment of the present invention, the sensitized ions are provided by a sensitized ion source, such as Yb. 3+ Ce 3+ 、Nd 3+ Gd 3+ Y 3+ At least one of the acetates.

[0017] According to an embodiment of the present invention, the molar ratio of sensitized ions to activated ions in the activated ion source and the sensitized ion source is (1-50):1, for example, 9:1 or 40:1.

[0018] According to an embodiment of the present invention, in the upconversion nanocrystals, the molar ratio of the sum of the molar amounts of the activating ions and the sensitizing ions to the molar ratio of the matrix material is 1:(1-20), for example, 1:10.

[0019] For example, the upconversion nanocrystals are NaYF4:Yb 3+ Er 3+ Among them, Yb 3+ and Er 3+ The molar ratio of Yb is 0.18:0.02, and its average particle size is 10-30 nm. Under 980 nm laser pumping, Yb... 3+ Sensitized Tm 3+ It emits a blue-purple upconversion glow.

[0020] For example, the upconversion nanocrystals are NaYF4:Yb 3+ Er 3+ Among them, Yb 3+ and Tm 3+ The molar ratio is 0.2:0.005, and the average particle size is 10-30 nm.

[0021] According to an embodiment of the present invention, the chiral template comprises a hydrogel formed by the self-assembly of amino acids, wherein the hydrogel contains helical nanofibers.

[0022] Preferably, the pitch of the nanofiber is 10-200 nm, for example, 130 nm or 135 nm.

[0023] According to an embodiment of the present invention, the chiral template has an excellent chiral spatial structure, including an L-configuration and a D-configuration.

[0024] According to an embodiment of the present invention, the amino acid is selected from a first amino acid and a basic amino acid.

[0025] According to an embodiment of the present invention, the first amino acid is selected from Fmoc-L-glutamic acid (Fmoc-L-Glu) and / or Fmoc-D-glutamic acid (Fmoc-D-Glu).

[0026] According to an embodiment of the present invention, the basic amino acid includes at least one of L-arginine (L-Arg), D-arginine (D-Arg), L-lysine (L-Lys), D-lysine (D-Lys), and L-histidine (L-His), D-histidine (D-His), preferably L-arginine (L-Arg) or D-arginine (D-Arg).

[0027] According to a preferred embodiment of the present invention, the chiral template comprises a hydrogel formed by self-assembly of amino acids, which contains left-helical nanofibers, wherein the amino acid is selected from at least one of Fmoc-L-glutamic acid (Fmoc-L-Glu), L-arginine (L-Arg), L-lysine (L-Lys), and L-histidine (L-His).

[0028] According to a preferred embodiment of the present invention, the chiral template comprises a hydrogel formed by self-assembly of amino acids, which contains right-handed helical nanofibers, wherein the amino acid is selected from at least one of Fmoc-D-glutamic acid (Fmoc-D-Glu) and D-arginine (D-Arg), D-lysine (D-Lys), and D-histidine (D-His).

[0029] For example, the chiral template comprises a hydrogel self-assembled from Fmoc-L-glutamic acid (Fmoc-L-Glu) and L-arginine (L-Arg), which contains left-handed helical nanofibers with a pitch of 130 nm.

[0030] For example, the chiral template comprises a hydrogel self-assembled from Fmoc-D-glutamic acid (Fmoc-D-Glu) and D-arginine (D-Arg) containing right-handed helical nanofibers with a pitch of 135 nm.

[0031] According to an embodiment of the present invention, in the luminescent material, the upconversion nanocrystals are uniformly distributed on the surface of the nanofibers in the chiral template.

[0032] According to an embodiment of the present invention, the luminescent material has the property of circularly polarized luminescence, such as CPL luminescence with multiple emission bands.

[0033] According to an embodiment of the present invention, the luminescence asymmetry factor (g) of the luminescent material is... lum At least 0.1 × 10 -2 For example, 0.1 × 10 -2 ~5×10 -2 For example, 0.5 × 10 -2 1×10 -2 2×10 -2 3.2×10 -2 .

[0034] This invention also provides a method for preparing the above-mentioned luminescent material, the method comprising the following steps:

[0035] (1) Synthesis of upconversion nanocrystals;

[0036] (2) Preparation of chiral templates;

[0037] (3) After mixing the upconversion nanocrystals obtained in step (1) with the chiral template in step (2), the mixture is heated and cooled to obtain the luminescent material.

[0038] According to an embodiment of the present invention, in step (1), the upconversion nanocrystals have the meaning as described above, and their preparation method is as follows: the raw materials, the activated ion source and the sensitized ion source are mixed in a stoichiometric ratio and prepared by high-temperature thermal decomposition.

[0039] According to an embodiment of the present invention, the raw material is selected from raw materials containing A and fluorine, and raw materials containing B. In the present invention, the raw material can be any substance known in the art, as long as it can prepare the upconversion nanocrystals.

[0040] For example, the raw material containing A and fluorine is sodium hydrofluoride.

[0041] For example, the raw material containing B is yttrium acetate.

[0042] According to an embodiment of the present invention, the activated ion source and the sensitized ion source have the meanings described above.

[0043] According to an embodiment of the present invention, the raw materials, the activating ion source, and the sensitizing ion source are mixed in an oily solvent. Preferably, the oily solvent is selected from oleic acid and / or octadecene.

[0044] According to an embodiment of the present invention, the conditions for high-temperature thermal decomposition can be those known in the art, and are not specifically limited in the present invention.

[0045] According to an embodiment of the present invention, the high-temperature thermal decomposition is carried out under nitrogen conditions.

[0046] According to an embodiment of the present invention, after high-temperature thermal decomposition, the carboxyl ligands on the surface of the upconversion nanocrystals can be washed away by acid washing.

[0047] According to an embodiment of the present invention, in step (1), the upconversion nanocrystals refer to an aqueous solution of the upconversion nanocrystals after acid washing.

[0048] According to an embodiment of the present invention, the concentration of the upconversion nanocrystals in the aqueous solution is 0.1-0.4 mg / mL, such as 0.1 mg / mL, 0.15 mg / mL, 0.2 mg / mL, 0.3 mg / mL or 0.4 mg / mL, but is not limited to the listed values, and other listed values ​​within this range are also applicable.

[0049] According to an embodiment of the present invention, in step (2), the chiral template has the meaning as described above, and its preparation method specifically includes: mixing amino acids with water, heating and cooling to obtain a hydrogel, which is the chiral template.

[0050] According to an embodiment of the present invention, the concentration of the amino acid in the hydrogel is 0.01-0.10 mol / L, for example 0.01 mol / L, 0.02 mol / L, 0.05 mol / L or 0.10 mol / L, but is not limited to the listed values, and other listed values ​​within this range are also applicable.

[0051] According to an embodiment of the present invention, the heating refers to heating until the amino acid molecules are completely dissolved.

[0052] According to an embodiment of the present invention, the cooling can be performed using conditions known in the art, and no specific limitations are made in this invention.

[0053] According to an embodiment of the present invention, the amino acids have the meanings described above, specifically including a first amino acid and a basic amino acid, which have the meanings described above.

[0054] Preferably, the molar ratio of the first amino acid to the basic amino acid is 0.1-1:0.1-1, for example, 1:1.

[0055] According to an embodiment of the present invention, in step (3), the mass-to-volume ratio of the chiral template hydrogel to the aqueous solution of the upconversion nanocrystals is 10-40 mg / mL, for example, 10 mg / mL, 15 mg / mL, 20 mg / mL, 30 mg / mL or 40 mg / mL, but not limited to the listed values, other listed values ​​within this range are also applicable.

[0056] According to an embodiment of the present invention, in step (3), the heating refers to heating until the upconversion nanocrystals are completely dissolved.

[0057] According to an embodiment of the present invention, in step (3), the cooling can be performed using conditions known in the art, and no specific limitation is made in the present invention.

[0058] Compared with existing solutions, the present invention has at least the following beneficial effects:

[0059] (1) The present invention provides a method for preparing a circularly polarized luminescent material, wherein the method can achieve upconversion circularly polarized luminescence of non-chiral upconversion nanocrystals through molecular self-assembly in rare earth upconversion nanocrystals and chiral template hydrogels;

[0060] (2) The present invention provides a method for preparing circularly polarized light-emitting materials based on rare earth upconversion nanocrystals, the method being able to achieve the emission of upconversion circularly polarized light in multiple bands;

[0061] (3) This invention provides a method for preparing circularly polarized luminescent materials based on rare earth upconversion nanocrystals. The preparation method is simple, operates at room temperature, has few environmental influences, and is low in cost. It is of great significance for studying the circularly polarized luminescence of inorganic nanomaterials. Attached Figure Description

[0062] Figure 1 Bright-field photograph (a) and small-angle X-ray powder diffraction pattern (b) of the hydrogel in Example 1;

[0063] Figure 2 Atomic force microscopy images of the hydrogel in Example 1;

[0064] Figure 3 Scanning electron microscope image of the hydrogel in Example 1;

[0065] Figure 4 Circular dichroism spectrum of the hydrogel in Example 1;

[0066] Figure 5 Transmission electron microscopy image of upconversion nanocrystals in Example 2;

[0067] Figure 6 X-ray powder diffraction pattern of upconversion nanocrystals in Example 2;

[0068] Figure 7 Fluorescence emission spectrum of upconversion nanocrystals in Example 2;

[0069] Figure 8 Transmission electron microscopy image of upconversion nanocrystals in Example 3;

[0070] Figure 9 X-ray powder diffraction pattern of upconversion nanocrystals in Example 3;

[0071] Figure 10 Fluorescence emission spectrum of upconversion nanocrystals in Example 3;

[0072] Figure 11 Small-angle X-ray powder diffraction pattern of a circularly polarized luminescent material;

[0073] Figure 12 X-ray powder diffraction pattern of circularly polarized luminescent material;

[0074] Figure 13 Transmission electron microscope image of a circularly polarized luminescent material;

[0075] Figure 14 The upconversion fluorescence emission spectrum of the circularly polarized luminescent material;

[0076] Figure 15 The CPL emission spectrum of a circularly polarized luminescent material;

[0077] Figure 16 The graph shows the calculated g-factor results for the emission position of the circularly polarized luminescent material.

[0078] Figure 17 The CPL emission spectrum of the circularly polarized luminescent material is shown. Detailed Implementation

[0079] The present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are merely illustrative and explanatory of the present invention, and should not be construed as limiting the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

[0080] Unless otherwise stated, the raw materials and reagents used in the following examples are commercially available products or can be prepared by known methods.

[0081] Instruments and equipment:

[0082] In this embodiment of the invention, the instrument used for powder diffraction characterization is a MiniFlex2 manufactured by Rigaku, and the copper target radiation wavelength is λ = 0.154187 nm.

[0083] The instrument used for transmission electron microscopy (TEM) in this embodiment of the invention is a TECNAI G. 2 F20, manufactured by FEI.

[0084] In this embodiment of the invention, the scanning electron microscope used for the inspection is model JSM-6700F, manufactured by JEOL.

[0085] The instrument used for atomic force microscopy in this embodiment of the invention is a Dimension Icon, manufactured by Bruker.

[0086] In this embodiment of the invention, the instrument used for circular dichroism spectroscopy characterization is a MOS-450, manufactured by Anton Paar.

[0087] In this embodiment of the invention, the instrument used for upconversion circular polarization fluorescence spectroscopy characterization is a CPL-300 manufactured by JASCO, and the excitation source is a 980nm semiconductor laser.

[0088] In this embodiment of the invention, the instrument used for upconversion fluorescence emission spectroscopy characterization is an FLS980 manufactured by Edinburgh, and the excitation source is a 980nm semiconductor laser.

[0089] Example 1: Preparation of chiral template hydrogels

[0090] The chiral template hydrogel can be prepared by heating and cooling an aqueous solution of small amino acid molecules, as follows:

[0091] (1) Weigh equal amounts of Fmoc-L-Glu and L-Arg powder into glass vials, and then add an appropriate amount of ultrapure water so that the total concentration of amino acid molecules in the vials is 0.05 mol / L.

[0092] (2) Place the bottle containing the mixed solution in a water bath and heat it at 90°C until all the amino acid molecules are dissolved to form a transparent aqueous solution.

[0093] (3) Remove the vial and cool it to room temperature to form an L-shaped hydrogel (L-Gel). Observe the flow of the hydrogel by inverting the vial.

[0094] Replace Fmoc-L-Glu with Fmoc-D-Glu and L-Arg with D-Arg in steps (1)-(3) above, and repeat the above method to prepare D-configuration hydrogel D-Gel.

[0095] The obtained hydrogels L-Gel and D-Gel were characterized. Figure 1 Figure a shows that Fmoc-L-Glu and L-Arg, and Fmoc-D-Glu and D-Arg, can form stable hydrogel structures with good light transmittance at a concentration of 0.05 mol / L; small-angle X-ray powder diffraction pattern ( Figure 1 (b) indicates that the hydrogel formed by the self-assembly of small amino acid molecules has a cross-layered bilayer structure; atomic force microscopy results ( Figure 2 The results showed that the L-Gel and D-Gel hydrogels were mainly composed of nanoscale helical fibers. Fmoc-L-Glu and L-Arg, and Fmoc-D-Glu and D-Arg formed left-handed and right-handed helical nanofibers, respectively, with pitches of approximately 130 nm and 135 nm. Scanning electron microscopy (SEM) Figure 3 This further confirms the presence of nano-helical fibers. Circular dichroism spectroscopy results show that ( Figure 4The hydrogels L-Gel and D-Gel possess excellent chiral spatial structures, with absorption asymmetry factors reaching up to 1.2 × 10⁻⁶. -2 .

[0096] Example 2: NaYF4:Yb 3+ Er 3+ Preparation of upconversion nanocrystals and their upconversion luminescence properties

[0097] NaYF4:Yb 3+ Er 3+ Upconversion nanocrystals can be prepared by high-temperature thermal decomposition, and the specific steps are as follows:

[0098] Acetate (specifically composed of 0.8 mmol yttrium acetate, 0.18 mmol ytterbium acetate, and 0.02 mmol erbium acetate) was mixed with 8 mL oleic acid and 12 mL octadecene in a 100 mL two-necked round-bottom flask. Nitrogen gas was bubbled through the flask to purge air, and the mixture was heated to 180 °C and stirred continuously for 30 min to allow the acetate to fully dissolve, resulting in a mixed solution. The solution was then allowed to cool naturally to room temperature. Next, 2 mmol sodium hydrofluoric acid powder was added to the mixed solution, and the solution was heated to 250 °C under a nitrogen stream and stirred continuously for 30 min to promote the decomposition of sodium hydrofluoric acid. The temperature was then raised to 310 °C and held constant for 60 min before allowing it to cool naturally to room temperature. After the reaction was complete, 20 mL ethanol was added and stirred thoroughly. The mixture was centrifuged at 12000 rpm for 5 min, and the reaction product was collected. The collected reaction product was washed three times with a mixture of 3 mL ethanol and 2 mL cyclohexane each time to obtain approximately 100 mg of upconversion nanocrystals. These nanocrystals were then redispersed in 5 mL cyclohexane to obtain NaYF4:Yb. 3+ Er 3+ A cyclohexane solution of upconversion nanocrystals is provided for further use.

[0099] In the upconversion nanocrystals of this embodiment, Yb 3+ and Er 3+ The doping amounts were 18% and 2%, respectively, and their transmission electron microscopy images ( Figure 5 ) and X-ray powder diffraction pattern ( Figure 6 This indicates that the upconversion nanocrystals are cubic NaYF4:Yb 3+ Er 3+ The structure exhibits good dispersibility and crystallization; the upconversion nanocrystals have a particle size of 10-20 nm (average particle size of 15 nm); the upconversion fluorescence emission spectrum indicates that in a 980 nm semiconductor laser (50 W / cm²), the upconversion nanocrystals can achieve high performance. 2 Under the excitation of NaYF4:Yb 3+ Er 3+ Upconversion nanocrystals at 540 nm ( 4 S3 / 2 → 4 I 15 / 2 ) and 650nm ( 2 F 9 / 2 → 4 I 15 / 2 It exhibits good green and red upconversion fluorescence emission at ( ) Figure 7 ).

[0100] Example 3: NaYF4:Yb 3+ ,Tm 3+ Preparation of upconversion nanocrystals and their upconversion luminescence properties

[0101] NaYF4:Yb 3+ ,Tm 3+ Upconversion nanocrystals can be prepared by high-temperature thermal decomposition, and the specific steps are as follows:

[0102] Acetate (composed of 0.8 mmol yttrium acetate, 0.2 mmol ytterbium acetate, and 0.005 mmol thulium acetate) was mixed with 8 mL oleic acid and 12 mL octadecene in a 100 mL two-necked round-bottom flask. Nitrogen gas was bubbled through the flask to purge air, and the mixture was heated to 180 °C and stirred continuously for 30 min to allow the acetate to dissolve completely, resulting in a mixed solution. The solution was then allowed to cool naturally to room temperature. Next, 2 mmol sodium hydrofluoric acid powder was added to the mixed solution, and the solution was heated to 250 °C under a nitrogen stream and stirred continuously for 30 min to promote the decomposition of sodium hydrofluoric acid. The temperature was then raised to 310 °C and held constant for 60 min before allowing it to cool naturally to room temperature. After the reaction was complete, 20 mL ethanol was added and stirred thoroughly. The mixture was centrifuged at 12000 rpm for 5 min, and the reaction product was collected. The collected reaction product was washed three times with a mixture of 3 mL ethanol and 2 mL cyclohexane each time to obtain approximately 100 mg of upconversion nanocrystals. These nanocrystals were then redispersed in 5 mL cyclohexane to obtain NaYF4:Yb. 3+ ,Tm 3+ A cyclohexane solution of upconversion nanocrystals is provided for further use.

[0103] Transmission electron microscope image of the upconversion nanocrystals in this embodiment ( Figure 8 ) and X-ray powder diffraction pattern ( Figure 9 This indicates that the upconversion nanocrystals are cubic NaYF4:Yb 3+ ,Tm 3+ The structure exhibits good dispersibility and crystallization; the upconversion nanocrystals have a particle size of 10-20 nm (average particle size of 15 nm); the upconversion fluorescence emission spectrum indicates that in a 980 nm semiconductor laser (50 W / cm²), the upconversion nanocrystals can achieve high performance. 2 Under the excitation of NaYF4:Yb 3+ ,Tm 3+Upconversion nanocrystals at 347nm ( 1 I6→ 3 F4), 362nm 1 D2→ 3 H6), 450nm 1 D2→ 3 F4) and 483nm 1 G4→ 3 It exhibits good blue upconversion fluorescence emission at H6. Figure 10 ).

[0104] Example 4: Preparation of Upconversion Nanocrystal Aqueous Solution

[0105] Upconversion nanocrystal aqueous solution can be prepared by acid washing, and the specific steps are as follows:

[0106] Mix 15 mL of anhydrous ethanol and 125 μL of concentrated hydrochloric acid in a conical flask to prepare a hydrochloric acid-ethanol solution with pH = 1. Then, take appropriate amounts of the upconversion nanocrystalline cyclohexane solutions from Examples 2 and 3, respectively, and sonicate them in the conical flasks for 20-30 min. After centrifugation at 12000 rpm for 10 min, further sonicate the precipitate in anhydrous ethanol and centrifuge again. Repeat this process 2-3 times until the precipitate after centrifugation is a transparent substrate precipitate. Disperse the precipitate in an appropriate amount of ultrapure water for later use. The acidified NaYF4:Yb... 3+ Er 3+ The concentration of the aqueous solution of upconversion nanocrystals was 20 mg / mL; the acidified NaYF4:Yb 3+ ,Tm 3+ The concentration of the aqueous solution of upconversion nanocrystals was 20 mg / mL.

[0107] Example 5:

[0108] The method for preparing circularly polarized luminescent materials by loading chiral hydrogels with achiral upconversion nanocrystals is as follows:

[0109] (1) Mix 1 mL of water with 10 μL of NaYF4:Yb 3+ Er 3+ Upconversion nanocrystals were mixed to obtain a diluted aqueous solution of upconversion nanocrystals, wherein NaYF4:Yb 3+ Er 3+ The concentration was 0.18 mg / mL;

[0110] (2) Mix the diluted aqueous solution of the upconversion nanocrystals from step 1 with 20 mg of hydrogel L-Gel from Example 1, heat until the hydrogel is completely dissolved, at which point the concentration of hydrogel L-Gel is 0.05 mmol / mL, cool, and the hydrogel-loaded non-chiral upconversion nanocrystals can be obtained, which is circularly polarized luminescent material-L1.

[0111] Example 6

[0112] The circularly polarized luminescent material in this embodiment is basically the same as in embodiment 5, except that the L-Gel hydrogel is replaced with D-Gel hydrogel to obtain the circularly polarized luminescent material -D1.

[0113] Example 7

[0114] The circularly polarized light-emitting material in this embodiment is basically the same as in Embodiment 5, except that: NaYF4:Yb 3+ Er 3+ Replace with NaYF4:Yb 3+ ,Tm 3+ The circularly polarized luminescent material -L2 was obtained.

[0115] Example 8

[0116] The circularly polarized light-emitting material in this embodiment is basically the same as in Embodiment 6, except that: NaYF4:Yb 3+ Er 3+ Replace with NaYF4:Yb 3+ ,Tm 3+ The circularly polarized luminescent material -D2 was obtained.

[0117] The circularly polarized luminescent materials prepared in Examples 5-8 were characterized, and the results are as follows:

[0118] Small-angle X-ray powder diffraction patterns of Examples 5-6 are shown below. Figure 11 As shown, the diffraction results of the circularly polarized luminescent material-D1 (UCNPs@D-Gel) are basically the same as those of the D-Gel hydrogel, and the diffraction results of the circularly polarized luminescent material-L1 (UCNPs@L-Gel) are basically the same as those of the L-Gel hydrogel, indicating that the addition of upconversion nanocrystals (UCNPs) did not destroy the bilayer film structure of the hydrogel (D-Gel or L-Gel).

[0119] The X-ray powder diffraction pattern of the circularly polarized luminescent material in Example 5 is shown below. Figure 12 As shown, the crystal phase of the upconversion nanocrystals in the hydrogel remains unchanged.

[0120] The transmission electron microscope (TEM) of the circularly polarized luminescent material in Example 5 is shown below. Figure 13 As shown, this indicates the distribution of upconversion nanocrystals on the surface of the helical fibers of the hydrogel.

[0121] The upconversion fluorescence spectra of the circularly polarized luminescent materials in Examples 5-8 are as follows: Figure 14 As shown, Figure 14 The diagram in section a indicates that hydrogels loaded with upconversion nanocrystals in circularly polarized luminescent materials can also be used in 980nm semiconductor lasers (50W / cm²).2 Er is generated under excitation 3+ At 540nm ( 4 S 3 / 2 → 4 I 15 / 2 ) and 650nm ( 2 F 9 / 2 → 4 I 15 / 2 Good green and red upconversion fluorescence emission at ( ) Figure 14 (b) Tm 3+ At 347nm ( 1 I6→ 3 F4), 362nm 1 D2→ 3 H6), 450nm 1 D2→ 3 F4) and 483nm 1 G4→ 3 Good blue upconversion fluorescence emission at H6) Figure 14 In (a), the fluorescence emission intensity is slightly lower than that of upconversion nanocrystals alone, which may be affected by light scattering in the gel medium;

[0122] The circularly polarized spectra of the circularly polarized luminescent materials in Examples 5-6 are as follows: Figure 15 As shown, this indicates that hydrogels loaded with upconversion nanocrystals can be used in a 980nm semiconductor laser (50W / cm²). 2 Under the excitation of Er 3+ and Tm 3+ A distinct circularly polarized emission signal was detected at the position of the emission peak. Figure 15 (a and b); by calculating the asymmetry factor value g at different launch positions. lum The maximum value can reach 3.2 × 10 -2 ( Figure 16 In this context, 'a' represents NaYF4:Yb. 3+ ,Tm 3+ The g-factor values ​​of the three emission bands after being combined with hydrogel, where b is NaYF4:Yb 3+ Er 3+ (g-factor values ​​for the three emission bands after being combined with hydrogel). As a control, the upconversion nanocrystals obtained in Example 4 were used in a 980nm semiconductor laser (50W / cm²). 2 Under excitation, no obvious signal is generated in the circularly polarized spectrum. Figure 17 This indicates that the generation of circularly polarized light is due to the chiral transfer between the helical fibers of the hydrogel and the upconversion nanocrystals.

[0123] The embodiments of the present invention have been described above. However, the present invention is not limited to the above embodiments. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a luminescent material, characterized in that, The preparation method includes the following steps: (1) Synthesizing upconversion nanocrystals, wherein the molecular formula of the upconversion nanocrystals is ABF4:(M, N), wherein A is selected from at least one of Na, Li, and K; B is selected from at least one of lanthanum, gadolinium, lutetium, yttrium, and scandium; and the activating ion M is Tm 3+ Or Er 3+ The sensitizing ion N is Yb. 3+ ; The raw materials, the activating ion source, and the sensitizing ion source are mixed in a molar ratio and then subjected to high-temperature thermal decomposition to prepare upconversion nanocrystals; the upconversion nanocrystals are then acid-washed to obtain an aqueous solution of upconversion nanocrystals. (2) Preparation of chiral template: Amino acids are mixed with water, heated and cooled to obtain hydrogel, which is the chiral template; (3) After mixing the aqueous solution of the upconversion nanocrystals obtained in step (1) with the chiral template in step (2), the mixture is heated and cooled to obtain the luminescent material; in the luminescent material, the upconversion nanocrystals are uniformly distributed on the surface of the nanofibers in the chiral template; The chiral template is a hydrogel formed by the self-assembly of amino acids. When the chiral template contains left-handed helical nanofibers, the amino acid is composed of at least one of Fmoc-L-glutamic acid, L-arginine, L-lysine, and L-histidine. When the chiral template contains right-handed helical nanofibers, the amino acid is composed of at least one of Fmoc-D-glutamic acid, D-arginine, D-lysine, and D-histidine.

2. The preparation method according to claim 1, characterized in that, The upconversion nanocrystals are uniform in size, with a particle size of 1-100 nm.

3. The preparation method according to claim 1, characterized in that, The activated ion source is Tm. 3+ Or Er 3+ Acetates; The sensitized ion source is Yb 3+ Acetates.

4. The preparation method according to claim 1, characterized in that, In the activated ion source and the sensitized ion source, the molar ratio of sensitized ions to activated ions is 1-50:1; In the upconversion nanocrystals, the molar ratio of the sum of the activating ions and the sensitizing ions to the molar ratio of the matrix material is 1:1-20.

5. The preparation method according to claim 1, characterized in that, The pitch of the nanofiber is 10-200 nm.

6. The preparation method according to claim 1, characterized in that, The luminescent material exhibits circularly polarized luminescence properties. The luminescence asymmetry factor of the luminescent material is at least 0.1 × 10⁻⁶. -2 .

7. The preparation method according to claim 1, characterized in that, In step (1), the raw materials are selected from raw materials containing A and fluorine, and raw materials containing B; The raw materials, the activating ion source, and the sensitizing ion source are mixed in an oily solvent; the oily solvent is selected from oleic acid and / or octadecene. The high-temperature thermal decomposition is carried out under nitrogen conditions.

8. The preparation method according to claim 1, characterized in that, In step (1), the acid washing refers to washing away the carboxyl ligands on the surface of the upconversion nanocrystals; in the aqueous solution of the upconversion nanocrystals, the concentration of the upconversion nanocrystals is 0.1-0.4 mg / mL.

9. The preparation method according to claim 1, characterized in that, In step (2), the concentration of the amino acid in the hydrogel is 0.01-0.10 mol / L.

10. The preparation method according to claim 1, characterized in that, In step (3), the chiral template has a mass concentration of 10-40 mg / mL in the aqueous solution of the upconversion nanocrystals.

Citation Information

Patent Citations

  • Perovskite nanocrystalline material with circularly polarized luminescence and up-conversion circularly polarized luminescence properties, preparation method and application thereof

    CN112430247A